2015
DOI: 10.5535/arm.2015.39.6.880
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Respiratory Muscle Strength and Conventional Sarcopenic Indices in Young Adults: A Preliminary Study

Abstract: ObjectiveTo investigate the relationships between respiratory muscle strength and conventional sarcopenic indices such as skeletal muscle mass and limb muscle strength.MethodsEighty-nine young adult volunteers who had no history of medical or musculoskeletal disease were enrolled. Skeletal muscle mass was measured by bioelectrical impedance analysis and expressed as a skeletal muscle mass index (SMI). Upper and lower limb muscle strength were evaluated by hand grip strength (HGS) and isometric knee extensor mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 39 publications
2
17
0
4
Order By: Relevance
“…The results of this study are also in conjunction with our previous study about the relationship between respiratory muscle strength and conventional sarcopenic indices in the young Korean population [ 28 ], in that respiratory muscle strength, markedly MIP, and various sarcopenic indices are inter-related, which is due to sarcopenia. In our previous study, MIP was the only value associated with SMM and limb muscle function.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study are also in conjunction with our previous study about the relationship between respiratory muscle strength and conventional sarcopenic indices in the young Korean population [ 28 ], in that respiratory muscle strength, markedly MIP, and various sarcopenic indices are inter-related, which is due to sarcopenia. In our previous study, MIP was the only value associated with SMM and limb muscle function.…”
Section: Discussionsupporting
confidence: 83%
“…Conversely, although our results showed a significant association between SMI and PE max , we found no significant association between SMI and PI max . In previous studies, investigators reported associations between SMI and PI max in young adults, between SMI and PE max in young men, and between SMI and PI max in healthy adults [13][14][15] . Therefore, there has been no consensus about which type of respiratory muscle, expiratory or inspiratory, is related to muscle mass.…”
Section: Discussionmentioning
confidence: 96%
“…However, only few studies have reported the effects of sarcopenia on respiratory muscle strength. Results of basic research suggest that skeletal muscle mass index (SMI) is related to the parameters of lung function and respiratory muscle strength in healthy young and older adults [13][14][15] . According to one report in Brazil, sarcopenia significantly reduced respiratory muscle strength 16) .…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip strength: It will be measured using a hand-grip dynamometer (T.K.K.5401; Takei Scientific Instruments, Tokyo, Japan),13 as described previously 14. Briefly, while sitting in a straight-backed chair with their feet flat on the floor, patients will be asked to adduct and neutrally rotate the shoulder, flex the elbow to 90° and place the forearm in a neutral position, with the wrist between 0° and 30° extension and between 0° and 15° ulnar deviation.…”
Section: Methods and Analysismentioning
confidence: 99%